2009
DOI: 10.1073/pnas.0904636106
|View full text |Cite|
|
Sign up to set email alerts
|

Kalirin regulates cortical spine morphogenesis and disease-related behavioral phenotypes

Abstract: Dendritic spine morphogenesis contributes to brain function, cognition, and behavior, and is altered in psychiatric disorders. Kalirin is a brain-specific guanine-nucleotide exchange factor (GEF) for Rac-like GTPases and is a key regulator of spine morphogenesis. Here, we show that KALRN -knockout mice have specific reductions in cortical, but not hippocampal, Rac1 signaling and spine density, and exhibit reduced cortical glutamatergic transmission. These mice exhibit robust deficits in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
200
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 153 publications
(210 citation statements)
references
References 50 publications
9
200
0
1
Order By: Relevance
“…The deficit in NMDA receptor levels did not prevent synapse formation in the developing brain of NR1-KD mice, but was sufficient to reduce spine density after adolescence, suggesting a greater necessity for intact NMDA receptor levels during synapse elimination or maintenance. Several recent studies illustrate how the cellular and behavioral consequences of developmental perturbations in neuron function may not become evident until adulthood (40)(41)(42)(43). Collectively, these studies and the present one demonstrate how genetic factors may act in an age-dependent fashion to produce adult-onset symptoms of CNS conditions associated with aberrant synaptic function.…”
Section: Discussionmentioning
confidence: 77%
“…The deficit in NMDA receptor levels did not prevent synapse formation in the developing brain of NR1-KD mice, but was sufficient to reduce spine density after adolescence, suggesting a greater necessity for intact NMDA receptor levels during synapse elimination or maintenance. Several recent studies illustrate how the cellular and behavioral consequences of developmental perturbations in neuron function may not become evident until adulthood (40)(41)(42)(43). Collectively, these studies and the present one demonstrate how genetic factors may act in an age-dependent fashion to produce adult-onset symptoms of CNS conditions associated with aberrant synaptic function.…”
Section: Discussionmentioning
confidence: 77%
“…Previous studies in Kalirin KO mice have found moderately reduced spine density in cortical neurons (19), but either no change (10,19) similarity, it is reasonable to infer that Kalirin and Trio serve similar roles in supporting synaptic structure. Interestingly, we found that knockdown of Kalirin or Trio expression individually resulted in a largely AMPAR-specific dysfunction, with NMDAR function mostly preserved, indicating that the total number of synapses in hippocampal CA1 pyramidal neurons is preserved by eliminating Kalirin or Trio alone.…”
Section: Discussionmentioning
confidence: 98%
“…Accordingly, Kidins220 is enriched at the postsynaptic density (Wu and Chao, personal communication), and dendriticspine stability is significantly reduced in Kidins220 -/+ mice (Wu et al, 2009). It is interesting in this context that Kalirin has a major role in dendritic-spine morphogenesis (Cahill et al, 2009;Ma et al, 2003;Ma et al, 2008;Penzes et al, 2003;Penzes and Jones, 2008), suggesting a new connection by Kidins220 between these pathways.…”
Section: Discussionmentioning
confidence: 99%